Spatial Structures and Spatial Patterns Formed by Tourism Activities on Tebing Breksi - Kusumaningrum, Noni; Kusumawardani, Neni (Journal of Indonesian Tourism and Development Studies, 2024)
Tebing Beksi is a former mining area that has been designated as a geological heritage site and is now used for tourism. Several tourism destination components have occupied the spaces of the Tebing Beksi area, resulting in a spatial distribution that forms a specific pattern worthy of deeper understanding. Therefore, this research is important for identifying and formulating spatial patterns that are formed by activities and the development/provision of tourism facilities and infrastructure. The research method used in this study is a qualitative descriptive method, which aims to provide a factual description, picture, or portrayal of the use of space. To compile the data analysis, a map is used as a guide to see the condition of the research object. This map primarily displays data on spatial conditions, specifically the locations of tourist destination components. Based on the analysis results, it can be observed that in tourist destination areas managed by local communities, several unplanned tourist facilities can be built spontaneously. This research explains why this could happen.